MOLECULAR DOCKING STUDY: TARGETING SICKLE CELL ANEMIA USING ACTIVE PHYTOCHEMICAL COMPOUNDS FROM ZANTHOXYLUM ZANTHOXYLOIDES - DAS, MOULI (Innovare Journal of Medical Sciences, 2023)
Objectives: A category of genetic disease which is sickle cell disease is called sickle cell anemia. In this, the red blood cells are affected in shape and structure, which normally carries oxygen to every part of our body. Therefore, by using molecular docking studies, Absorption, Distribution, Metabolism, and Excretion (ADME) analysis for phytocompounds, an effort was made to find natural compounds from a plant named Zanthoxylum zanthoxyloides, which has many medicinal properties in Indian Ayurveda, to prevent this genetic disease. Methods: The Protein Data Bank database was used to retrieve the primary protein, hemoglobin. The PyRx tool was used to perform docking because the ligands were poorly binding with the compounds and were interfering with the docking, so this tool was used. Swiss-ADME and the Admetlab web server were used for the analysis of ADME and drug similarity. Results: Five chemicals from Z. zanthoxyloides have been identified through molecular docking investigations as having high binding affinity to the protein by inhibiting the replication of viruses and proteolytic cleavage. Out of these five compounds, Benz[c]acridine, Fagaramide trans-fagaramide was safe and possessed drug-like qualities according to the ADMET profile and drug similarity prediction. Conclusion: According to the current study, Benz[c]acridine and Fagaramide trans-fagaramide have a particular binding affinity and aid in the management of treatment approaches for treating sickle cell anemia.